TURNING THE TIDE ON INDONESIA'S FOOD WASTE CRISIS: A GENERATION Z-LED MOVEMENT - Avicenna, Fitria; Wifka Rahma Syauki (UPT. PKM UB, 2023)
Indonesia faces a serious issue related to food waste, which is a significant problem in the economic, environmental and social sectors. Food waste accounts for a large part of the composition of waste in landfills and produces methane gas which contributes to the climate crisis. This community service activity partners with Garda Pangan, which is a movement that seeks to address the problem of food waste with a holistic approach, focusing on reducing food loss and food waste and providing access to food for the underprivileged. With various activities such as collecting donated food from food businesses, tackling food waste from major events, and conducting policy advocacy, Garda Pangan hopes to reduce the problem of food waste in Indonesia and create a society that is more aware of the importance of reducing food wastage for environmental sustainability and social welfare. . Through this webinar, Generation Z, represented by students, shows an increased awareness of food waste which is mostly produced by households and wishes to change habits to reduce the food waste they produce every day. In an effort to reduce food waste, the majority of respondents chose to reduce buying impulse snacks, while some also chose to bring food/drink containers to take the leftovers home if they didn't run out.